Case Report: Encephalitis, with Brainstem Involvement, Following Checkpoint Inhibitor Therapy in Metastatic Melanoma. (30th May 2017) - Bossart, Simon; Thurneysen, Selina; Rushing, Elisabeth; Frontzek, Karl; Leske, Henning; Mihic‐Probst, Daniela; Nagel, Hannes W.; Mangana, Johanna; Goldinger, Simone M.; Dummer, Reinhard
Abstract : Checkpoint inhibitors are increasingly being used in the treatment of malignant melanoma and other cancers. With the use of such therapies, autoimmune‐mediated adverse events in the central and peripheral nervous system are likely to occur more frequently. We report a unique case of brainstem encephalitis with a sudden lethal outcome following ipilimumab and pembrolizumab therapy in a patient with malignant melanoma. The autopsy showed a diffuse nodular activation of microglia in the whole encephalon with prominent intraparenchymal and perivascular lymphocytic infiltration of the brainstem. Non‐infectious brainstem encephalitis is a well‐recognized subset of paraneoplastic encephalitis. Brainstem involvement is usually accompanied by a wide spectrum of signs and symptoms, which were not observed in this case. The timing of the clinical symptoms as well as the histopathological findings suggest an autoimmune‐adverse event of ipilimumab and pembrolizumab administration rather than a paraneoplastic disorder. In the presence of neurological symptoms, immediate cessation of the immunotherapy and immunosuppressive therapy may lead to successful therapeutic intervention, as described in previous reports. Therefore, it is crucial that physicians are aware of the possible side effects of immunotherapies on the nervous system. Abstract : A unique case of brainstem encephalitis, in a patient with malignant melanoma being treated with ipilimumab and pembrolizumab, is reported.